Menilik Peran Pesantren dan Madrasah dalam Menangkal Radikalisme di Indonesia - Arif Syamsurrijal (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Education, both formal and non-formal, has a very vital role in the process of deradicalization in Indonesia. However, education can also be a forum for radicalism to emerge, considering that there are several schools that are made